‘Pele de sapo’ melon grown under different irrigation depths and bioestimulant rates in the Semiarid region of Brazil - Souza Reis Lima, Daíse; Lima Simões, Welson; Bezerra da Silva, José Aliçandro; Nascimento Amorim, Magno do; Monteiro Salviano, Alessandra; Duarte Costa, Nivaldo (Comunicata Scientiae, 2020)
The objective of this work was to evaluate physiological and biochemical responses of Pele de sapo melon to different irrigation depths (ID) and bioestimulant rates (BTM) to improve its production efficiency. The experiment was conducted in an experimental field in Juazeiro, BA, Brazil. A randomized block design in split split-plot arrangement was used, with four ID (60, 80, 100, and 120% of crop evapotranspiration – ETc) in the plots; five (BTM) (Stimulate® at 0, 0.6, 1.2, 2.4, and 4.8 L ha-1 applied via irrigation system during the flowering stage and after the fruiting stage) in the subplots; and two crop seasons (hot season, 23 to 39 °C; and cold season, 15 to 30 °C) in the sub-subplots. The plants were under daily drip irrigation and spacing of 2.0 × 0.3 m. The variables evaluated were: gas exchange, water use efficiency, chlorophyll a and b, relative water, sugar, and amino acid contents, and fruit yield. The results showed that the ID of 60% ETc resulted in water deficit, denoted by increases in solute concentrations, whereas the ID of 80% and 100% resulted in plants with good performance for biochemical, physiological, and production parameters in both crop seasons. The hot season, ID of 120% ETc, and BTM of 2.4 L ha-1 are recommended for Pele de sapo melon crops, since they result in the best physiological responses and fruit yields.